Safety and efficacy of selective RIPK1 inhibitor SIR1-365 in hospitalized patients with severe COVID-19: A multicenter, randomized, double-blind, phase 1b trial - Norberto Chavez-Tapia; Muneeba Ahsan Sayeed; Shobha Luxmi; Douglas J. Kasper; Fenchao Xue; Yang Shen; Weiliang Fan; Wei Yuan; Bin Du (Journal of Intensive Medicine)
Background: Receptor-interacting protein kinase 1 (RIPK1), a serine/threonine protein kinase, is mainly activated by pro-inflammatory cytokines and pathogens, including severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and its activation could result in apoptosis, necroptosis, or inflammation. This study was conducted to evaluate the safety and efficacy of a potent and selective inhibitor of RIPK1, SIR1-365, in hospitalized patients with severe coronavirus disease 2019 (COVID-19). Methods: This multicenter, randomized, double-blind, phase 1b study screened patients from December 18, 2020 until November 27, 2021. Adults hospitalized with severe COVID-19 (diagnosed ≤2 weeks before screening) were randomized 1:1 to receive oral placebo or SIR1-365 100 mg three times daily for ≤14 consecutive days, with standard-of-care. The primary objective was to evaluate SIR1-365 safety and tolerability. Secondary objectives included an assessment of SIR1-365 efficacy. Descriptive statistics were used to summarize safety. The study was not powered for efficacy testing. Relevant inferential statistical tests were used to aid interpretation of differences in clinical efficacy. Results: Forty-five patients were randomized, 42 were treated. Eighteen patients experienced treatment-emergent adverse events (TEAEs) and 7 patients were ≥ grade 3. Fewer SIR1-365-treated vs. placebo-treated patients experienced TEAEs (30.4% vs. 57.9%) and serious TEAEs (13.0% vs. 26.3%) within 28 days of the first dose. There were no serious treatment-related TEAEs or deaths. Compare to placebo, SIR1-365 significantly increased arterial oxygenation from baseline to day 7 (least-squares mean change [standard error]: 109.4 [26.4] vs. -24.2 [23.6]; P=0.0095), significantly reduced hospitalization duration after treatment (mean±standard deviation: [4.7±3.7] days vs. [8.6±5.6] days; P=0.0145) and respiratory failure incidence (8.3% vs. 38.1%; two-sided P=0.0291) during the study, and numerically shortened the time to clinical improvement in World Health Organization ordinal scale (median: 5.0 days vs. 9.0 days, P=0.0766). Conclusions: SIR1-365 was well tolerated and demonstrated a trend toward quicker recovery than placebo in hospitalized patients with severe COVID-19.Trial Registration ClinicalTrials.gov number: NCT04622332